The expression h-rhwy in Thamudic B inscriptions from north west Arabia - Norris, Jérôme (Proceedings of the Seminar for Arabian Studies, 2017)
This contribution studies six new Thamudic B graffiti discovered between TaymāΜ and ДāΜil (north-west Saudi Arabia), which contain the phrase h-rhwy, bringing the total number of known texts with this expression to sixteen. This is likely to be a nisbah (gentilic adjective), ‘the Rhwite’, expressing the author’s affiliation to a social group. As almost all these inscriptions are associated with drawings of horses and camels, however, this interpretation has been called into question. It has, on the one hand, been suggested that the gentilic could also be that of the animal depicted, probably as an indication of its origin or breed. On the other hand, some scholars have considered the possibility that rhwy could instead be a verbal adjective meaning ‘swift’ or ‘ambling’, describing the animal’s walk or function. These various hypotheses are examined in light of the information provided by the six new texts and a rereading of those previously published. It is argued that h rhwy should definitively be understood as a nisbah, that of a local lineage group named Rhw.